MISI GEREJA DALAM KONTEKS PLURALITAS DI INDONESIA - Hariprabowo, Yakobus (UNIKA Santo Thomas, 2003)
Proclamation is the permanent priority of mission. Church cannot elude Christ's explicit mandate, nor deprive men and women of the